2016
DOI: 10.1123/jpah.2015-0666
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Moderate-to-Vigorous Physical Activity in Brazilian Children

Abstract: Several factors were identified as correlates of MVPA in Brazilian children; however, only travel mode to school was common for both boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 0 publications
3
33
0
7
Order By: Relevance
“…Los resultados del presente estudio compararon las varianzas en variables de intensidad de la actividad física medida con acelerómetros y monitores de frecuencia cardiaca tomando en cuenta el género y el porcentaje de grasa corporal, los valores encontrados reportaron con una p menor a α≤ 0.005 con diferencias significativa solo en la clase de educación física entre las medias de la actividad física moderada a vigorosa (hombres: 0,003; mujeres: 0,001) y la frecuencia cardiaca (hombres: 0,001, mujeres: 0,000) en los sujetos con porcentaje de grasa corporal normal en comparación a los sujetos con porcentaje de grasa corporal alta los presentes datos corroboran lo reportado en investigaciones realizadas con diseño metodológico similar donde asocian de manera inversamente proporcional la actividad física moderada vigorosa realizada por niños y niñas con su porcentaje de grasa corporal 22,23 .…”
Section: Comparación De La Actividad Física Por Género Y Grasa Corporunclassified
“…Los resultados del presente estudio compararon las varianzas en variables de intensidad de la actividad física medida con acelerómetros y monitores de frecuencia cardiaca tomando en cuenta el género y el porcentaje de grasa corporal, los valores encontrados reportaron con una p menor a α≤ 0.005 con diferencias significativa solo en la clase de educación física entre las medias de la actividad física moderada a vigorosa (hombres: 0,003; mujeres: 0,001) y la frecuencia cardiaca (hombres: 0,001, mujeres: 0,000) en los sujetos con porcentaje de grasa corporal normal en comparación a los sujetos con porcentaje de grasa corporal alta los presentes datos corroboran lo reportado en investigaciones realizadas con diseño metodológico similar donde asocian de manera inversamente proporcional la actividad física moderada vigorosa realizada por niños y niñas con su porcentaje de grasa corporal 22,23 .…”
Section: Comparación De La Actividad Física Por Género Y Grasa Corporunclassified
“…Studies have shown that boys perceive a higher prevalence of the presence of some attribute for PA than girls 6,15,17,30 . Findings also indicate that boys accumulate more time in leisure PA than girls 15,33 . In general, perceiving the presence of spaces near one's home can facilitate engagement in PA 4,9 .…”
Section: First Author Region Variables Resultsmentioning
confidence: 82%
“…Complete data for the outcomes of interest and all investigated correlates were available for 328 children. Missing data were found for 256 participants of the original sample of participants 17 .…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear why adiposity development might be more sensitive to variation in physical activity in boys than in girls, but it is possible that influences on the energy-intake side of the energy-balance equation may be more important in girls than boys. In particular, low physical activity is considered in children as significant correlates of excess body fat 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation